Phospholipid Transport via Mitochondria. (12th July 2014) - Tamura, Yasushi; Sesaki, Hiromi; Endo, Toshiya
<x xml:space="preserve">Abstract</x> In eukaryotic cells, complex membrane structures called organelles are highly developed to exert specialized functions. Mitochondria are one of such organelles consisting of the outer and inner membranes (OM and IM) with characteristic protein and phospholipid compositions. Maintaining proper phospholipid compositions of the membranes is crucial for mitochondrial integrity, thereby contributing to normal cell activities. As cellular locations for phospholipid synthesis are restricted to specific compartments such as the endoplasmic reticulum (ER) membrane and the mitochondrial inner membrane, newly synthesized phospholipids have to be transported and distributed properly from the ER or mitochondria to other cellular membranes. Although understanding of molecular mechanisms of phospholipid transport are much behind those of protein transport, recent studies using yeast as a model system began to provide intriguing insights into phospholipid exchange between the ER and mitochondria as well as between the mitochondrial OM and IM. In this review, we summarize the latest findings of phospholipid transport via mitochondria and discuss the implicated molecular mechanisms. <inline-graphic xlink:href="ark:/27927/pgh11r1h4mt" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />